2019
DOI: 10.1111/infa.12287
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Maternal Postpartum Depression, Infant Social Behavior With a Stranger, and Infant Cognitive Development

Abstract: Maternal postpartum depression (PPD) has been found to be related to infant social withdrawal during mother–infant interaction, and this may spill over on infant interactive behavior in other social contexts and impact infant psychosocial development. We investigated whether PPD was associated with infant social withdrawal during interaction with a tester in a psychological test situation and whether infant social withdrawal in the test situation mediated the association between PPD and infant cognitive scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
(36 reference statements)
2
10
0
3
Order By: Relevance
“…NCU teams should consider ways to overcome these barriers given that it is established in the evidence base that maternal postpartum distress can affect infant socio‐emotional and cognitive development (e.g. see Smith‐Nielsen, Lange, Wendelboe, von Wowern, & Væver, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…NCU teams should consider ways to overcome these barriers given that it is established in the evidence base that maternal postpartum distress can affect infant socio‐emotional and cognitive development (e.g. see Smith‐Nielsen, Lange, Wendelboe, von Wowern, & Væver, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2010) reported a kappa ranging from inadequate to excellent and Moe et al (2016) reported on Cohen's K that was good to excellent. Puura et al (2019) and Smith-Nielsen et al (2019) found an ICC that was excellent. Some support for construct validity has been found in these studies where ADBB has been linked to shared pleasure (Puura et al, 2019), maternal sensitivity (Puura et al, 2013), postpartum depression (Smith-Nielsen, 2019), as well as group differences between full-term and preterm babies in ADBB score (Moe et al, 2016).…”
Section: Evaluation Of the Documentation (Reliability Validity And No...mentioning
confidence: 93%
“…The PsykTestBarn review included one Norwegian article by Braarud and colleagues (2013), who found some inconsistent results regarding construct validity and concluded that the examination of the psychometric properties of the ADBB in Scandinavia was not satisfactory. Other Nordic studies not included in the PsykTestBarn review were from Norway (Moe et al, 2016), Denmark (Smith-Nielsen et al, 2019), and Finland (Puura et al, 2007, 2010.…”
Section: Evaluation Of the Documentation (Reliability Validity And No...mentioning
confidence: 99%
“…In contrast, sustained social withdrawal may have adverse effects on child development, since this behavior limits the infant's access to the social learning environment (Guedeney et al, 2013 ). Indeed, studies have shown that social withdrawal in infancy is associated with less optimal outcomes within several developmental domains, such as emotional and behavioral disorders (Guedeney et al, 2014 ; Zhou et al, 2021 ) and poorer cognitive and language development (Milne et al, 2009 ; Guedeney et al, 2017 ; Smith-Nielsen et al, 2019 ).…”
Section: Why Is Social Withdrawal Behavior In Infants Important To Co...mentioning
confidence: 99%